PENDIDIKAN INKLUSIF DARI PESANTREN - Huda, Anwari Nuril (Idrak: Journal of Islamic Education, 2018)
Since the last decade, the Indonesian education system has undergone a significant orientation  change, namely from  segregation education  towards  towards  inclusive education that strives to provide education services for people with disabilities in regular education institutions (non-SLB). In many public education institutions, the implementation of inclusive education experiences paradigmatic and technical constraints, which has implications for the low process of transforming institutions into an inclusive education system. On the  other hand, Indonesia has an  Pesantren as institution that has proven to be able to play a strategic role in the history of education. The institution also holds a lot of potential that can be used as a basic material for building  inclusive education.  Through its  wealth,  pesantren  can  design  inclusive education quickly, distinctively and classically.